HUBUNGAN ANTARA EMOTIONAL INTELLIGENCE (EI) DAN ORGANIZATIONAL COMMITMENT (OC) GURU SEKOLAH DASAR (SD) SWASTA SURABAYA BARAT - Yuliati Nur Rohmah; Windasari (Universitas Negeri Surabaya, 2022)
This study discusses the description of emotional intelligence and the organizational commitment of teachers at Private Elementary Schools in West Surabaya and the relationship between the variables of emotional intelligence and organizational commitment. This research is a type of descriptive and correlation research with a quantitative approach. The sample in this study were 91 teachers from West Surabaya Private Elementary Schools. The location of this research was conducted at 19 private elementary schools in West Surabaya. Data collection used the emotional intelligence scale which has sub-variables recognizing self-emotions, managing self-emotions, motivating oneself with empathy, and forming relationships as well as the organizational commitment scale which has affective commitment, continuance commitment and normative commitment sub-variables. Data analysis was carried out through frequency and TCR tests to determine the level of emotional intelligence and organizational commitment of teachers and through the Spearman correlation test to determine the magnitude of the relationship and the direction of the relationship between the two variables. The results of the study show that the level of emotional intelligence and organizational commitment of teachers is included in the good category and the relationship between the two variables is included in the strong and positive category. Keywords Emotional Intelligence, Organizational Commitment, West Surabaya Private Elementary School